EFEKTIVITAS SEDUHAN DAUN ASAM JAWA TERHADAP KADAR HOMA-IR DAN HOMA-β PADA PASIEN DIABETES MELLITUS TIPE 2 - Nopriantini, Nopriantini; Purba, Jonni Syah R; Desi, Desi; Petrika, Yanuarti; Novia, Devi; Ihsan, Bagus Muhammad (Poltekkes Kemenkes Bandung, 2024)
This study assessed the impact of tamarind leaf tea on HOMA-IR and HOMA-β levels in patients with Type 2 Diabetes Mellitus (DM). Thirty-two patients aged 20-50 years from Sungai Ambawang District Health Center, who were not using any DM medication, participated. They were divided into control (KN) and treatment (KP) groups, with KP receiving a tamarind leaf tea infusion for 7 days. HOMA-IR and HOMA-β levels were calculated using standardized formulas based on fasting insulin and glucose levels. The Wilcoxon signed-rank test revealed a significant decrease in HOMA-IR levels in the KP group (p<0.05), while no significant change was observed in the KN group. Although no significant difference in HOMA-β levels was found between the two groups, the KP group showed a notable increase by 4. These findings suggest that a 7-day tamarind leaf tea infusion effectively reduced HOMA-IR levels in patients with type 2 DM, although it did not significantly affect HOMA-β levels. This study highlights the potential of tamarind leaf tea as a complementary approach for managing insulin resistance in Type 2 DM patients. Further research is needed to explore the long-term effects and mechanisms of action for improving β-cell function. The conclusion of this study is that steeping tamarind leaves for seven days can reduce HOMA-I levels and slightly increase HOMA-β levels in patients with type 2 Diabetes Mellitus.